Cost-effectiveness of scaling up short course preventive therapy for tuberculosis among children across 12 countries. (January 2021) - Jo, Youngji; Gomes, Isabella; Flack, Joseph; Salazar-Austin, Nicole; Churchyard, Gavin; Chaisson, Richard E.; Dowdy, David W.
Abstract: Background: While household contact investigation is widely recommended as a means to reduce the burden of tuberculosis (TB) among children, only 27% of eligible pediatric household contacts globally received preventive treatment in 2018. We assessed the cost-effectiveness of household contact investigation for TB treatment and short-course preventive therapy provision for children under 15 years old across 12 high TB burden countries. Methods: We used decision analysis to compare the costs and estimated effectiveness of three intervention scenarios: (a) status quo (existing levels of coverage with isoniazid preventive therapy), (b) contact investigation with treatment of active TB but no additional preventive therapy, and (c) contact investigation with TB treatment and provision of short-course preventive therapy. Using country-specific demographic, epidemiological and cost data from the literature, we estimated annual costs (in 2018 USD) and the number of TB cases and deaths averted across 12 countries. Incremental cost effectiveness ratios were assessed as cost per death and per disability-adjusted life year [DALY] averted. Findings: Our model estimates that contact investigation with treatment of active TB and provision of preventive therapy could be highly cost-effective compared to the status quo (ranging from $100 per DALY averted in Malawi to $1, 600 in Brazil; weighted average $383 per DALY averted [uncertainty range: $248 – $1, 130]) and preferred to contact investigation without preventive therapy (weighted average $751 per DALY averted [uncertainty range: $250 – $1, 306]). Key drivers of cost-effectiveness were TB prevalence, sensitivity of TB diagnosis, case fatality for untreated TB, and cost of household screening. Interpretation: Based on this modeling analysis of available published data, household contact investigation with provision of short-course preventive therapy for TB has a value-for-money profile that compares favorably with other interventions. Funding: Unitaid (2017–20-IMPAACT4TB).